2015
DOI: 10.1038/srep08509
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 siRNA loaded hyaluronic acid-based CD44 targeted nanoparticle systems circumvent paclitaxel resistance in ovarian cancer

Abstract: Development of multidrug resistance (MDR) is an almost universal phenomenon in patients with ovarian cancer, and this severely limits the ultimate success of chemotherapy in the clinic. Overexpression of the MDR1 gene and corresponding P-glycoprotein (Pgp) is one of the best known MDR mechanisms. MDR1 siRNA based strategies were proposed to circumvent MDR, however, systemic, safe, and effective targeted delivery is still a major challenge. Cluster of differentiation 44 (CD44) targeted hyaluronic acid (HA) base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 52 publications
(88 reference statements)
6
90
0
Order By: Relevance
“…Recently, siRNA technology has been widely used in basic research to understand the function of a specific gene and has also been used as a clinical therapeutic approach to cure a specific disease. [11][12][13][14] Doxorubicin (DOX) is a common chemotherapy medication used to treat many kinds of cancers, such as breast cancer, bladder cancer, and lymphoma. [15][16][17][18][19] DOX interacts with DNA leading to a break in the DNA strand, which blocks DNA transcription and replication, resulting in apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, siRNA technology has been widely used in basic research to understand the function of a specific gene and has also been used as a clinical therapeutic approach to cure a specific disease. [11][12][13][14] Doxorubicin (DOX) is a common chemotherapy medication used to treat many kinds of cancers, such as breast cancer, bladder cancer, and lymphoma. [15][16][17][18][19] DOX interacts with DNA leading to a break in the DNA strand, which blocks DNA transcription and replication, resulting in apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies on PEGylated PEI-based nanovectors found varying results, possibly due to the differing molecular weights of PEI or PEG, 21,33) different ratios of PEG and PEI, and different methods of conjugation. 21) A further factor may be the addition of other compounds, such as bioinspired phosphorylcholine, 34) hyaluronic acid, 35) cyclic RGD, 36) and γ-polyglutamic acid. 37) Consequently, further studies on these modifications could achieve even more efficient, specific PEI-based nanovectors.…”
Section: Discussionmentioning
confidence: 99%
“…HA incorporated nanocarriers can deliver traditional chemotherapeutic drugs, such as doxorubicin and cyclosporine, to successfully target CD44 expressing CSCs both in vitro and in vivo [75]. This Nanomedicine based CSC targeting strategies have achieved prolonged survival in multiple animal cancer models including AML [76,[100][101][102][103]. Antibody incorporated nanocarriers have also been used for CSC targeting.…”
Section: Targeting Lscs By Nanomedicinementioning
confidence: 99%